IMPLEMENTATION OF ACTIVE LEARNING STRATEGY AS AN EFFORT TO INCREASE STUDENT ACTIVITY IN CLASS - Indra Geni; Neviyarni; Herman Nirwana (Literasi Nusantara, 2021)
In the learning process in the classroom, there are many methods that can improve and achieve maximum learning goals. Of the many existing methods to increase student learning activity in the classroom, namely the active learning strategy. Moving on from the observations the researchers did related to the activeness of students in the class, it was still not optimal. It can be in the form of still a few students who are independent in learning, less asking the teacher or asking the teacher during the learning process. To increase student activity in the learning process in this class, the researchers conducted research related to the application of active learning strategies as an effort to increase student activity in class. In its implementation, the learning model can be developed in 8 stages of the learning process, namely: (1) Orientation, (2) Group Formation, (3) Group Work Assignments, (4) Exploration, (5) Presentation of material in class (6) Understanding Checking and Material deepening, (7) Reflection and feedback, (8) Formative Evaluation.